(untitled) (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2016)
The present study aims to analyze the accounting professionals’ point of view as opposed to the students and master students’ one, regarding the creative accounting phenomenon existence and manifestation forms. In order to accomplish this objective, there has been used the poll/investigation, as a research method and the questionnaire, as a research instrument. Within the study, there is suggested the testing of more hypotheses that contribute to the clarifying of the aspects wished to be analyzed through the research. These hypotheses’ acceptance or rejection is based on the "chi-squareâ€– (Karl Pearson) statistical test and rank ordering method. Trying to elaborate a global conclusion of the questionnaire, there could be noticed the fact that over 50% from the questioned accounting students are not tempted to use the creative accounting practices and techniques in order to optimize the taxation without breaking the actual law regulations. At the opposite side, more than a half from the questioned accounting professionals would use these practices without breaking the law regulations that lead to the taxation’s optimization. The creative accounting has a negative connotation if the accurate image of the financial position and of the performance is not targeted because it represents the essential factor for elaborating and grounding the accounting policies. However, the positive side of the creative accounting is not excluded, given that one appeals to the "fairâ€– professional judgment of the accounting professionals and to the good faith of managers.